FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA ROOM ATTENDANT DEPARTEMENT HOUSEKEEPING DI COMFORT HOTEL DUMAI - Wijayanti, Rizki Ayu; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Performance is a work acheived by an employee in accordance with the standards and criteria that have been determined within a certain time. This study aims to determine the factors that affect the performance of room attendant in Comfort Hotel Dumai and find out what factors that dominate the performance of room attendant in Comfort Hotel Dumai. As the factors discussed in this case are individual factors, Psychological factors, and organizational factors. This research was conducted in June until July 2017 and located in Comfort Hotel Dumai. Design this research using quantitative method with descriptive approach. The sample used is 8 respondents and the data obtained through the questionnaire by using likert scale as measuring tool to determine the lenght of the interval. based on the results of the research that has been done, that the above three factors do affect the performance of room attendant in comfort hotel dumai, namely individual factors, psychological factors and organizational factors. And the most dominant factors in influencing the performance of room attendant in Comfort Hotel Dumai is psychological factors.Keywords: human resource, performance, room attendant, hotel.